Penyuluhan Komunikasi Interpersonal Orang Tua Asuh Dalam Membentuk Karakter dan Kepribadian Anak Asuh di Panti Asuhan Al-Akbar Kota Pekanbaru (STMIK Dharmapala Riau, 2023)
This Community Service activity was carried out at LKSA Al-Akbar Orphanage, Maharatu District, Pekanbaru city. In this This Community Service activity, the target is LKSA administrators who also act as foster parents for foster children at LKSA Al-Akbar Orphanage Pekanbaru. This Community Service activities are a form of counseling, discussion, socialization by providing education to the caretaker or foster parents at the Al-Akbar orphanage regarding the pattern of interpersonal communication in shaping the character and personality of the foster children at the Al-Akbar orphanage. In addition, it is also a good way of communicating with foster children who have reached the age of teenagers who have begun to be difficult to manage and are starting to be affected by bad associations outside the orphanage.